Função social do contrato: Um limite imposto à liberdade contratual - Moreira, Carolina Xavier da Silveira (2005)
The Social Role of the Contract analyses this institute through the historical evolution of contractual freedom, from its regulation however implicit in the 1988 s Federal Constitution, to its explicitness through the 2002 s Civil Code. It shows the different points of view about the subject, jutting out the existent diversities, such as: a) the range of the social role of the contract; b) the attenuation of the relativity principle and the contract mandatory power without prejudice to the contract essence maintenance; and c) its application beyond the legal issue regulated by the Civil Code. The Social Role of the Contract proposes an open concept for this new institution and analyzes the recent jurisprudence about the subject showing some of the several existent application possibilities. The conclusions about the subject, as any matter in Law, are relative and intended only to clarify the approach adopted in this dissertation, and do not disregard the importance of the arguments by those who defend ideas contrary to the ones presented here.